(untitled) (Research, Society and Development, 2020)
Jambu is a plant of great economic importance in Northern Brazil due to its gastronomic, medicinal use and currently of great interest to the cosmetics industry. However, studies on the nutrition aspects of this culture are still incipient. Thus, it was aimed that this work test the use of biofertilizer based on goat manure in cover on the growth and production of jambu. The experimental design used was a randomized block in a 4x4 factorial with four replications. The treatments consisted of water: bioliquid proportions, identified as 1: 1, 2: 1 and 3: 1, and a control treatment (without fertilization) combined with four evaluation dates (7, 14, 21, and 28 days after transplantation-DAT). Shoot length and fresh weight, fresh leaf weight, and productivity were evaluated. Based on the results, it was observed that the application of the biofertilizer in coverage influenced the growth and production of jambu throughout the collection period, with emphasis on formulations with a higher proportion of biofertilizer evaluated at 28 DAT. In this way, fertilization with biofertilizer in cover promotes and can be considered an important fertilization strategy for the cultivation of jambu.